Enzyme-replacement therapy with agalsidase alfa in children with Fabry disease - Ries, Markus; Clarke, Joe T. R.; Whybra-Trümpler, Catharina; Timmons, Margaret; Robinson, Chevalia; Schlaggar, Bradley L.; Pastores, Gregory; Lien, Y. Howard; Kampmann, Christoph; Brady, Roscoe Owen; Beck, Michael; Schiffmann, Raphael (Pediatrics, 2006)
CONTEXT. Fabry disease is an X-linked multisystem disorder. Enzyme-replacement therapy in adults has limited efficacy in treating major sequelae of advanced Fabry disease, such as kidney failure or stroke. This prompted a study of the safety and efficacy of enzyme replacement at an earlier stage of Fabry disease. - OBJECTIVES. Our purpose with this work was to evaluate safety and to explore efficacy of enzyme treatment with agalsidase alfa in pediatric patients with Fabry disease. - METHODS. We conducted a 6-month open-label study at 3 tertiary care centers with 24 children (19 boys and 5 girls) with a mean age of 11.8 (range: 6.5-18) years, to examine safety parameters, including infusion reactions and antiagalsidase alfa antibodies. - RESULTS. Agalsidase alfa was well tolerated, and all of the patients completed the study. Six boys and 1 girl had mild-to-moderate infusion reactions. One boy developed transient immunoglobulin G antibodies against agalsidase alfa. The boys showed a significant reduction in plasma globotriaosylceramide on treatment. Mean estimated glomerular filtration rate, cardiac structure, and function were normal and did not change over 26 weeks. Heart rate variability, as determined by 2-hour ambulatory monitoring, was decreased in the boys compared with the girls at baseline. All indices of heart rate variability improved significantly in the boys. Three patients with anhidrosis, as determined by quantitative sudomotor axon reflex testing, developed sweating. Six of 11 patients could reduce or cease their use of antineuropathic analgesics. - CONCLUSIONS. Enzyme replacement with agalsidase alfa was safe in this study. The exploratory efficacy analysis documented increased clearance of globotriaosylceramide and improvement of autonomic function. Prospective long-term studies are needed to assess whether enzyme replacement initiated early in patients with Fabry disease is able to prevent major organ failure in adulthood.
Gesehen am 15.05.2019